The Role of Character Education in Building Ethics and Morality among Students in the Digital Age - Marwan, Marwan; Hasbullah, Bahmid; Rahayu, Indah; Wakhudin, Wakhudin; Saputra, Dedi Gunawan (PT Inovasi Pratama Internasional, 2025)
This investigation aims to analyze the role of character education in fostering students' ethics and morality within the digital era.Utilizing a qualitative approach, this study explores the experiences of educators, students, and parents in implementing character education within formal educational environments.Data were gathered through in-depth interviews, participatory observation, and document analysis.The findings indicate that character education exerts a substantial influence in enhancing students' ethical awareness and moral reasoning, particularly in navigating ethical challenges stemming from digital technology exposure. Nevertheless, the study also uncovers significant barriers to this goal, including the lack of value-based technology support and time constraints. The study's findings suggest that a collaborative effort among schools, families, and communities is essential to maximize the impact of character education in the digital era.